The study of the surface roughness of photopolymer composite materials polymerized according to different techniques - Mykyyevych, N. (Actual Dentistry, 2018)
Objective. To conduct the comparative evaluation of the surface roughness of different micro-hybrid photopolymer materials, polymerized with UV radiation (direct restoration) or with UV radiation and temperature exposure (indirect restoration). Materials and Methods. Five samples of each material made with layering UV polymerization (first group) and with additional thermal processing in Cure Lite Plus under the temperature of 120°С during 10 minutes have been under analysis. Micro roughness has been detected in an atomic force microscope Solver P 47 (Germany) in a contact mode with the probe curve radius of 10 nm, which identified its resolution. Results. Materials Charisma and Filtek Z 250 have shown the best results among the samples with direct restoration, the difference being subtle (40.1 and 44.5 nm correspondingly). Dipol has demonstrated the worst results with the difference of 82.8 nm. Among the indirect restorations the surface of the composite material Charisma has turned out to be the smoothest (35.6 nm). Filtek Z 250 has shown slightly worse results with 42.6 nm. The average roughness of the surface of the samples from material Dipol has appeared to be the most prominent. Conclusions. The study has proved that indirect restorations can be better polished and can longer preserve smooth surface, which prevents dental plague and bacterial colonization. Key words: photopolymer composite materials, direct and indirect restoration, surface roughness.